Migration Crises in 21st Century Africa Patterns, Processes and Projections - Adeniran, Adebusuyi Isaac; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Palgrave Macmillan, 2020)
Migration Crises in 21st Century Africa explores the ever-expanding crises of migrations from various regions of Africa to other parts of the world; notably the pattern that utilizes the pre-existing trans-Saharan trade route via North Africa and the Mediterranean to Europe$1 (Bs southern fringes. Dr. Adebusuyi Isaac Adeniran explores key interrelated factors in astonishing depth, examining the nature of mobility in pre-modern African society; the impact of governance structures, demographics and economics; and the roles of both state and non-state actors. Adeniran additionally interrogates possible interventions and considers what the future of mobility within and beyond the boundaries of Africa might look like in an increasingly mobile world. Dr. Adebusuyi Isaac Adeniran is Associate Professor in sociology, migration and development studies at Obafemi Awolowo University, Nigeria. He is also Visiting Scholar at The Harriet Tubman Institute, York University, Canada and a Research Consultant to the United Nations Office on Drugs and Crime.s
Chapter 1. Introduction: Reflecting on the Practice of Migration in Africa -- Chapter 2. Failed Governance: The Foundation of a Culture of Irregular Migration in 21st Century Africa -- Chapter 3. African Demographic Dividend, Migration-Development Nexus and Global Economic Reality -- Chapter 4. Contextualizing the Humanistic Interventions of State and Non-State Actors in the Migration Crises -- Chapter 5. The Improbable and the Sustainable Remedies -- Chapter 6. The Future of Migration in (and beyond) Africa -- Chapter 7. Concluding Comments.
Keywords: Emigration and immigration; Human geography; Migration; Human Geography